2018
DOI: 10.1002/jsfa.9127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rearing substrate on growth performance, waste reduction efficiency and chemical composition of black soldier fly (Hermetia illucens) larvae

Abstract: Vegetable and fruit wastes and winery by-products can be used as rearing substrates for BSF larval mass production. Brewery by-products led to very promising larval performance and nutritional composition. However, given BRE limited availability, low BRE dietary inclusion levels could be used with the purpose of increasing larval performance. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

48
288
11
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 379 publications
(417 citation statements)
references
References 46 publications
48
288
11
7
Order By: Relevance
“…However, a higher pupation ratio and a lower substrate reduction rate were observed in the BSFL reared on food waste treated with PS and PE microplastics, compared to the control. Previous studies have been reported for the decomposition of diverse organic wastes including fruit and vegetable mixture and pig manure using BSFL, and the growth and development of BSFL differed depending on the substrates employed (Jucker et al 2017;Liu et al 2018;Meneguz et al 2018); this is not surprising given that various substrates including food waste have heterogenous traits in their composition (Hossain et al 2014). More studies are required to apply BSFL in processing of diverse types of food waste.…”
Section: Discussionmentioning
confidence: 99%
“…However, a higher pupation ratio and a lower substrate reduction rate were observed in the BSFL reared on food waste treated with PS and PE microplastics, compared to the control. Previous studies have been reported for the decomposition of diverse organic wastes including fruit and vegetable mixture and pig manure using BSFL, and the growth and development of BSFL differed depending on the substrates employed (Jucker et al 2017;Liu et al 2018;Meneguz et al 2018); this is not surprising given that various substrates including food waste have heterogenous traits in their composition (Hossain et al 2014). More studies are required to apply BSFL in processing of diverse types of food waste.…”
Section: Discussionmentioning
confidence: 99%
“…Insects as novel, alternative feed ingredients has now become a worldwide, well-recognized research topic in animal nutrition, because of their excellent nutritive properties and peculiar rearing characteristics [14,15]. Indeed, insects contain high quality and quantity of protein [14] and they can easily be reared on several organic side streams, thus reducing their environmental and economic impact and allowing their transformation into high-protein feeds [15].…”
Section: Introductionmentioning
confidence: 99%
“…Starting from July 2017, the European Commission has approved the use of insect meals (IM) as protein sources in aquaculture [12]. Compared to FM and other alternative protein sources, the IM production has some advantages: insects can convert low value organic wastes into protein and fat [13], their production leads to lower emission of greenhouse gases, and they have a lower water footprint [14]. From a nutritional point of view, IM are rich in proteins, with a good essential amino acid (EAA) profile, and they have a good content of fat, vitamins, and minerals [15].…”
Section: Introductionmentioning
confidence: 99%